Correlation of Reading Interest with Writing Ability of STIKOM Students Yos Sudarso Purwokerto - Monika Gisthi Secaresmi; David Kristiaan Paath; Wilibrordus Megandika Wicaksono; Adit Setiawan; Siti Maskanah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the correlation between reading interest and writing ability of STIKOM Yos Sudarso Purwokerto students as an effort to understand the relationship between two basic literacy skills in the context of higher education. Low interest in reading is often blamed as one of the causes of students' weak writing skills, which impacts their academic quality and critical thinking skills. This study aims to determine the extent to which reading interest affects students' writing skills, as well as provide an initial mapping of literacy conditions in the campus environment. The method used is quantitative with a correlational approach. Data was collected through questionnaires to measure reading interest levels and writing tests to assess students' writing ability. The analysis was carried out by Pearson correlation statistical test. The results of the study showed a significant positive correlation between students' reading interest and writing ability. The higher the students' interest in reading, the better their writing skills, especially in terms of writing structure, vocabulary use, and logical argumentation. These findings reinforce the assumption that active reading habits can promote significant improvements in writing skills. Therefore, a learning strategy is needed that is able to foster a literacy culture among students.